1999
DOI: 10.1097/00007632-199912010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Information and Advice to Patients With Back Pain Can Have a Positive Effect

Abstract: This trial shows that carefully selected and presented information and advice about back pain can have a positive effect on patients' beliefs and clinical outcomes, and suggests that a study of clinically important effects in individual patients may provide further insights into the management of low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(138 citation statements)
references
References 25 publications
2
130
2
4
Order By: Relevance
“…The current situation in Booklets are a simple, cheap, and popular method of providing health-related information to patients [30], and have been shown to be feasible and effective in low back pain [4,10]. More generally, studies have suggested that such material can improve compliance [15], alleviate anxiety and promote psychological well being [23], and reduce medical negligence claims [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current situation in Booklets are a simple, cheap, and popular method of providing health-related information to patients [30], and have been shown to be feasible and effective in low back pain [4,10]. More generally, studies have suggested that such material can improve compliance [15], alleviate anxiety and promote psychological well being [23], and reduce medical negligence claims [39].…”
Section: Discussionmentioning
confidence: 99%
“…This followed the general philosophy and style of The Back Book [56], which has been shown to be highly acceptable to health professionals and patients, and effective in changing patient beliefs and improving functional outcomes [4,10]. The main aim of the present booklet was to improve understanding, reduce uncertainty and anxiety, promote positive expectations and beliefs, and build confidence during post-operative recovery.…”
Section: Development Of the Bookletmentioning
confidence: 99%
“…After the seminar, soldiers were involved in a question and answer session and issued The Back Book [27]. The Back Book was used as the educational supplement, because of our prior experience with it in a physical therapy clinical trial [12] and its prior association with positive shifts in patient LBP beliefs [8,10].…”
Section: Psychosocial Educational Program (Psep)mentioning
confidence: 99%
“…Psychosocial education that encourages positive coping was associated with decreased work absence in a quasi-experimental study [34]. The Back Book [27] is a pamphlet that delivers standard, evidencedbased information consistent with a biopsychosocial model, and has been used in randomized clinical trials demonstrating reduced disability and fear-avoidance beliefs in general practice [8] and physical therapy settings [12]. A quasi-experimental study also indicated that general practice patients given the Back Book reported higher patient satisfaction ratings and lower rates of persistent LBP [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate information should be given to the patient, as many myths and prejudices exist. 22 Once serious disease has been excluded, it should be explained to the patient that there is little likelihood of serious complications and that the term "simple back pain" is commonly used. Provide the patient with the most safe and effective methods of symptom control.…”
Section: Provision Of Patient Informationmentioning
confidence: 99%